2017
DOI: 10.1075/pc.17006.par
|View full text |Cite
|
Sign up to set email alerts
|

Gestures of the abstract

Abstract: Speakers perform manual gestures in the physical space nearest them, called gesture space. We used a controlled elicitation task to explore whether speakers use gesture space in a consistent way (assign spaces to ideas and use those spaces for those ideas) and whether they use space in a contrastive way (assign different spaces to different ideas when using contrastive speech) when talking about abstract referents. Participants answered two questions designed to elicit contrastive, abstract discourse. We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…The systematic use of gesture space also extends to abstract referents, e.g., ideas, emotions, and discourse elements (Parrill and Stec, 2017). A corpus study of English contrastive gestures showed that speakers regularly produce gestures to each side of space when contrasting two ideas (Hinnell, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The systematic use of gesture space also extends to abstract referents, e.g., ideas, emotions, and discourse elements (Parrill and Stec, 2017). A corpus study of English contrastive gestures showed that speakers regularly produce gestures to each side of space when contrasting two ideas (Hinnell, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…One novelty of this study is the examination of gesture use in a non-spatial context, which is different from earlier evidence that focused on the relation between gesture production and spatiality (but see, Hurtienne et al, 2010;Parrill & Stec, 2017;Zdrazilova et al, 2018). Studies repeatedly emphasised that gestures are particularly effective in thinking and communicating about visual and spatial information (e.g., Alibali, 2005;Feyereisen & Havard, 1999;Lavergne & Kimura, 1987).…”
Section: Discussionmentioning
confidence: 88%
“…For each spoken element in a contrast or list, we coded first whether it was accompanied by a gesture. There are many definitions of gesture, which can include movements of the entire upper body, such as head tilts and hand gestures (Parrill & Stec, 2017; Wehling, 2009). In Study 1, we focused specifically on hand gestures, defined as symbolic movement of the hands and arms in order to accompany the speech (Peters & Hoetjes, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…For each spoken element in a contrast or list, we coded first whether it was accompanied by a gesture. There are many definitions of gesture, which can include movements of the entire upper body, such as head tilts and hand gestures (Parrill & Stec, 2017;Wehling, 2009).…”
Section: Gesture Codingmentioning
confidence: 99%